Ligneous amendments increase soil organic carbon content in fine-textured boreal soils and modulate N2O emissions - Peltokangas, Kenneth; Kalu, Subin; Huusko, Karoliina; Havisalmi, Jimi; Heinonsalo, Jussi; Karhu, Kristiina; Kulmala, Liisa; Liski, Jari; Pihlatie, Mari (PloS one, 2023)
Organic soil amendments are used to improve soil quality and mitigate climate change. However, their effects on soil structure, nutrient and water retention as well as greenhouse gas (GHG) emissions are still poorly understood. The purpose of this study was to determine the residual effects of a single field application of four ligneous soil amendments on soil structure and GHG emissions. We conducted a laboratory incubation experiment using soil samples collected from an ongoing soil-amendment field experiment at Qvidja Farm in south-west Finland, two years after a single application of four ligneous biomasses. Specifically, two biochars (willow and spruce) produced via slow pyrolysis, and two mixed pulp sludges from paper industry side-streams were applied at a rate of 9–22 Mg ha -1 mixed in the top 0.1 m soil layer. An unamended fertilized soil was used as a control. The laboratory incubation lasted for 33 days, during which the samples were kept at room temperature (21°C) and at 20%, 40%, 70% or 100% water holding capacity. Carbon dioxide (CO 2 ), nitrous oxide (N 2 O) and methane (CH 4 ) fluxes were measured periodically after 1, 5, 12, 20 and 33 days of incubation. The application of ligneous soil amendments increased the pH of the sampled soils by 0.4–0.8 units, whereas the effects on soil organic carbon content and soil structure varied between treatments. The GHG exchange was dominated by CO 2 emissions, which were mainly unaffected by the soil amendment treatments. The contribution of soil CH 4 exchange was negligible (nearly no emissions) compared to soil CO 2 and N 2 O emissions. The soil N 2 O emissions exhibited a positive exponential relationship with soil moisture. Overall, the soil amendments reduced N 2 O emissions on average by 13%, 64%, 28%, and 37%, at the four soil moisture levels, respectively. Furthermore, the variation in N 2 O emissions between the amendments correlated positively with their liming effect. More specifically, the potential for the pulp sludge treatments to modulate N 2 O emissions was evident only in response to high water contents. This tendency to modulate N 2 O emissions was attributed to their capacity to increase soil pH and influence soil processes by persisting in the soil long after their application.